Efficiency of Iron- and Calcium-Impregnated Biochar in Adsorbing Phosphate From Wastewater in Onsite Wastewater Treatment Systems - Dalahmeh, Sahar S.; Stenström, Ylva; Jebrane, Mohamed; Hylander, Lars D.; Daniel, Geoffrey; Heinmaa, Ivo (Frontiers in Environmental Science, 2020)
This study evaluated the potential of biochar impregnated with Fe3+ or Ca2+, or mixed with Polonite®, as a filter material for removal of phosphate (PO4-P) from wastewater in onsite wastewater treatment systems (OWTS). Four treatments with biochar were investigated: unimpregnated biochar (UBC), biochar impregnated with iron Fe3+ (FBC), biochar impregnated with calcium oxide (CBC), and biochar mixed with Polonite® (PBC). In a batch experiment using phosphate solution at concentrations 0.5, 3.3, 6.5, 13, and 26 mg PO4-P L–1, adsorption of PO4-P in the different treatments was modeled using Langmuir and Freundlich isotherms. Column filters (5 diameter × 55 cm height) packed with UBC, FBC, CBC, and PBC were then furnished with raw wastewater over 148 weeks. During this experiment, adsorption of PO4-P was investigated in response to increasing hydraulic loading rate (HLR; 56, 74, and 112 L m–2 day–1) and increasing phosphate loading rate (PLR; 195, 324, 653, and 1715 mg PO4-P m–2 day–1). Among the materials, FBC had the highest maximum adsorption capacity (Qm) based on Langmuir isotherms (3.21 ± 0.01 mg g–1). FBC and CBC showed robust performance with increasing HLR, while increasing PLR increased the amount of PO4-P retained in all filters. After 148 weeks of operation, removal of PO4-P (averaged over the last 18 weeks of operation) was 13 ± 16% for UBC, 40 ± 20% for CBC, 88 ± 12% for FBC, and 30 ± 18% for PBC. The PO4-P amount retained in filters over the 148 weeks was 84.75, 221.75, 358.38, and 152.36 g m–2 in UBC, CBC, FBC, and PBC, respectively. The adsorption capacity of the filters after 148 weeks was 1.50, 4.02, 6.41, and 2.75 mg g–1 for UBC, CBC, FBC, and PBC, respectively. The adsorption capacity values and breakthrough curves showed that low concentrations (i.e., <2.6 mg L–1) of PO4-P in wastewater would allow the FBC filter to remain active for 58 months and the CBC filter for 15 months, before PO4-P removal declined to <70%. In conclusion, biochar impregnated with iron and calcium is a promising solution for removal of PO4-P from wastewater in OWTS.